Teachers’ assessment literacy: the impact of gender, education, training, and work experience - Muhson, Ali; Mwakapemba, James Leonard; Siswanto, Siswanto; Prilanita, Yeni Nur; Susilowati, Nenden (Journal of Education and Learning (EduLearn), 2025)
Assessment literacy is an essential part of the teaching and learning process. Good assessment practices will have an impact on the quality of learning outcomes. The purpose of this study is to investigate assessment literacy among educators and identify the effects of gender, education, training, and work experience. A random sample of 134 teachers participated in this exploratory study. Tests and questionnaires have been employed in data collection methods. The data were analyzed using dummy variable regression analysis. This study found that teachers' assessment literacy was poor. Gender and training had an impact on assessment literacy, while education and work experience had no bearing on it. A more in-depth study with a wider scope needs to be conducted to gain a more comprehensive insight into teachers' assessment literacy. It is also worth studying in more depth what factors are thought to influence teachers’ assessment literacy.